A Zona Incerta no sagüi (Callithrix jacchus): Análise Citoarquitetônica, Neuroquímica e Projeção Retiniana - Lima, Raissa Rodrigues de (2008)
The retinal projections in mammals usually reach, classically, three major functional systems: the primary visual system, the accessory optic system, and the circadian timing system. But the retinal projections also reach areas classically considered non-visual, one of which groups the neurons of the zona incerta (ZI), target this study. The primary visual system includes thalamic lateral geniculate complex is formed by the dorsal lateral geniculate nucleus, intergeniculate leaflet and the ventral lateral geniculate nucleus and other Components. The accessory optic system is composed of the small nuclei: nuclei terminal dorsal, lateral, medial and the interstitial nucleus of the superior posterior fasciculus. These nuclei are involved in visuo-motor activities. The circadian timing system is comprised of the suprachiasmatic nucleus of the hypothalamus, that act as master circadian pacemaker, entraining pathways and efferents pathways to the efectors, and the intergeniculate leaflet, that seems to act as a modulator of the pacemaker. The retinal projections too reach classically considered non-visual areas, including the zona incerta. This region is localized in the ventral thalamus and has been implicated in various functional properties including nociceptive and somatosensory processing, motor response, sociosexual behaviour, feeding and drinking, in symptoms of neurodegenerative diseases, arousal and attention. It also displays connection with several areas of central nervous system. The aim of this study was characterize the retinal projection in the zona incerta of Callithrix jacchus (sagüi), a primate of the New World through the anterograde axonal transport of the cholera toxin subunit b and analyze the citoarchicteture using Nissl and NeuN, and neurochemical substances such as serotonin, GABA, VIP, VP, GFAP and binding-calcium proteins. The zona incerta showed a different division of the literature in citoarquitetura, both by means of Nissl as neurochemical by NeuN, with a subdivision ventrolateral and dorsomedial. The neurochemical to the other substances corroborate with this subdivision. The GFAP was almost completely negative for the zona incerta, result non evidenced in previous studies yet. The 16 retinal projection in sagüi, unlike other primates and rodents, reached the caudal portion only. This work helps to make further studies are conducted based on this subdivision and the localization of the neurochemical substances associated with possible behaviors that the zona incerta is involved